The long and winding road of climate-resilient development: a case study–driven analysis of shocks, policy strategies, and individual reactions in Austria - Claudia Winkler; Sebastian Seebauer; Sabrina Dreisiebner-Lanz; Thomas Thaler; Hermine Mitter; Eva Posch; Theresa Gorbach; Robert Steiger; Bernadette Kropf (Regional Environmental Change, 2026)
Ongoing and future climate change impacts call for climate-resilient development that integrates adaptive and mitigative approaches. Climatic and non-climatic shocks, which are rare and disruptive events, might promote transformative changes and effectively improve climate resilience. Following the IPCC’s concept of Climate Resilient Development Pathways (CRDPs), we use document analysis and semi-structured interviews with n = 41 stakeholders and n = 46 affected individuals to analyse three case studies in Austria: residential relocation after a flood, agricultural water management during a multi-seasonal drought, and tourism investments during the COVID-19 pandemic. The case studies track policy strategies and individual reactions across three distinct phases: strategy development prior to the shock, strategy application during the shock, and strategy impact following the shock. The shocks revealed that the existing policy strategies may fix or at least alleviate the policy problems in the short term but do not catalyse the entry into CRDPs. Several policy strategies were adapted and implemented to support affected individuals but are not transformed by the shocks. The policy strategies mostly fail to promote climate resilience because of disconnected governance levels, fragmented sectoral perspectives, and a lack of horizontal policy coordination. If individuals realise measures that are effective for both climate change adaptation and mitigation, they do so on their own accord and are not triggered by specific policy instruments. Shocks do not emerge as distinct milestones on CRDPs. Future climate-resilient policy strategies should include binding regulations, regional differentiation, and flexibility for individual needs.

Agronomy is paramount: A case study on the mismatch between farm-scale measures and policy instruments for drought adaptation in Seewinkel, Austria - Sabrina Dreisiebner-Lanz; Claudia Winkler; Sebastian Seebauer (Journal of Environmental Management, 2026)

Welfare and inequality impacts of carbon pricing and compensation schemes on fuel poor households in Styria, Austria - Veronika Kulmer; Dominik Kortschak; Judith Köberl; Sebastian Seebauer (Energy and Climate Change, 2025)

Under which conditions can shocks stimulate transformative recovery: the Strategy Shock Implementation Reaction (SSIR) framework - Sebastian Seebauer; Eva Posch; Thomas Thaler; Claudia Winkler; Hermine Mitter (Mitigation and Adaptation Strategies for Global Change, 2025)
Future shocks from climate change impacts will likely overstretch current individual coping capacities. Integrated policy strategies could foster sustainable and resilient reactions of households and businesses by rebuilding for transformative recovery instead of bouncing back to the pre-shock status. We present the Strategy Shock Implementation Reaction (SSIR) framework as a conceptual framework for bridging the design of policy strategies to their implementation after a shock and the following reactions of the affected households and businesses. We illustrate the SSIR framework using examples of climate resilience pathways that integrate climate change adaptation and mitigation policy: planned relocation and building renovation. The framework details how a shock converts a strategy and how this conversion influences the strategy’s effect on individual reactions. It thus re-conceptualizes shocks from mere policy windows to policy filters. We discuss how the framework may be operationalized in research on how policy strategies evolve and function over time.

Feeling hot is being hot? Comparing the mapping and the surveying paradigm for urban heat vulnerability in Vienna - Sebastian Seebauer; Michael Friesenecker; Thomas Thaler; Antonia E. Schneider; Stephan Schwarzinger (Science of The Total Environment, 2024)

How path dependency manifests in flood risk management: observations from four decades in the Ennstal and Aist catchments in Austria - Sebastian Seebauer; Thomas Thaler; Susanne Hanger-Kopp; Thomas Schinko (Regional Environmental Change, 2023)
Path dependency occurs when a contingent event predetermines what further steps can be taken and self-reinforcing mechanisms lock-in any further development on a sub-optimal trajectory. Path dependency is a prominent concept in the adaptation pathways literature, but insufficiently defined and operationalised. The present paper empirically tracks all constitutive elements of path dependency for four decades of flood risk management (FRM) in two alpine mountain regions in Austria, the Ennstal and Aist river catchments, using a mixed-methods approach. FRM governance has a critical role whether decisions lead to path dependency. Lock-in manifests not just in technical structures, but also in inertia of incumbent actor coalitions and management paradigms. Sub-optimality is hard to assess for lack of clearly defined protection targets; however, it appears in the ways that structural measures are implemented—too little, too late or with negative impacts on nature conservation. Past floods do not qualify as contingent events, as they have not fundamentally changed FRM practice. By contrast, technological and institutional shifts over longer periods, such as digital hazard maps and EU directives, have gradually reoriented FRM strategies. Institution-based self-reinforcing mechanisms are more prevalent than technology-based self-reinforcing mechanisms. Established actor coalitions combined with institutional density illustrate how those in charge uphold a path to defend their position, power and resources. Our recommendations for how to overcome path dependency in FRM governance are: encourage niche experiments, link FRM more closely with climate change adaptation, revise the national policy framework towards polycentric governance approaches and improve professional training.

Correction to: Coping strategies and trajectories of life satisfaction among households in a voluntary planned program of relocation from a flood-risk area - Sebastian Seebauer; Claudia Winkler (Climatic Change, 2020)

Coping strategies and trajectories of life satisfaction among households in a voluntary planned program of relocation from a flood-risk area - Sebastian Seebauer; Claudia Winkler (Climatic Change, 2020)